Prenatal Ethanol Exposure Leads to Attention Deficits in Both Male and Female Rats - Wang, Ruixiang; Martin, Connor D.; Lei, Anna L.; Hausknecht, Kathryn A.; Ishiwari, Keita; Richards, Jerry B.; Haj-Dahmane, Samir; Shen, Roh-Yu (Frontiers in Neuroscience, 2020)
Background. Prenatal ethanol exposure (PE) causes multiple behavioral and cognitive deficits, collectively referred to as fetal alcohol spectrum disorders (FASD). Studies show that 49 – 94% of FASD children exhibit attention deficits, even when they have normal IQs or lack severe facial deformities, suggesting that attention deficits could be caused by even moderate prenatal exposure to alcohol, of which the underlying neural mechanisms are still unclear. A valid rodent model could help elucidate this phenomenon. Material and Methods. A second-trimester equivalent binge drinking PE model was utilized. Pregnant Sprague Dawley rats were administered with 15% (w/v) ethanol (6 g/kg/day, via gastric gavage) during gestational days 8 – 20, and their offspring were the subjects in the present study. A modified 2-choice reaction time (2-CRT) task was used to illustrate possible attention deficits, including increased action impulsivity and lapses of attention. Enhanced impulsivity was reflected by more premature responses while increased lapses of attention were manifested as more incorrect responses and/or greater variability of reaction time, demonstrated by more skewed distributions of reaction time. Ten-week-old male and female rats were tested for 3 sessions following 16 – 19 days’ training. Results. Our PE paradigm caused no major teratogenic effects. Prenatal ethanol exposure led to increased impulsivity exhibited as greater premature responses and augmented lapses of attention shown by greater skewnesses of reaction time distributions, relative to controls. The deficits were observed in both PE male and female rats. Interestingly, in males, the attention deficits were detected only when the 2-CRT task was relatively difficult whereas in females they were detected even when the task was at a less demanding level. Conclusion. We show that the binge drinking pattern of PE led to attention deficits in both sexes of rats even though no major teratogenic effects were observed. Therefore, this rodent model can be used to study neural mechanisms underlying attention deficits caused by PE and to explore effective intervention approaches for FASD.